2020
DOI: 10.48550/arxiv.2010.03829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyper-regular graphs and high dimensional expanders

Ehud Friedgut,
Yonatan Iluz

Abstract: Let G = (V, E) be a finite graph. For d 0 > 0 we say that G is d 0 -regular, if every v ∈ V has degree d 0 . We say that G is (d 0 , d 1 )-regular, for 0for every 1 ≤ i ≤ n − 1, the joint neighborhood of every clique of size i is d i -regular); In that case, we say that G is an n-dimensional hyper-regular graph (HRG). Here we define a new kind of graph product, through which we build examples of infinite families of n-dimensional HRG such that the joint neighborhood of every clique of size at most n − 1 is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this work we also analyze partite tensor products of simplicial complexes as defined in [FI20]. We show that a partite tensor product of a k-partite β-coboundary expander with a complete k-partite complex is also a β • exp(−O(k))-coboundary expander.…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we also analyze partite tensor products of simplicial complexes as defined in [FI20]. We show that a partite tensor product of a k-partite β-coboundary expander with a complete k-partite complex is also a β • exp(−O(k))-coboundary expander.…”
Section: Open Questionsmentioning
confidence: 99%
“…and then pairing them by color. This operation on simplicial complexes was defined by [FI20] which also observed that a link of a (k…”
Section: Some Simple Coboundary Expandersmentioning
confidence: 99%